2007
DOI: 10.1016/j.juro.2006.10.034
|View full text |Cite
|
Sign up to set email alerts
|

A Histone Deacetylase Inhibitor Enhances Adenoviral Infection of Renal Cancer Cells

Abstract: In human renal cancer specimens a loss of or decrease in coxsackie and adenovirus receptor expression may be an early event in renal cancer progression. Pretreatment with FK-228 may increase tumor cell sensitivity to adenoviral gene therapy vectors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 13 publications
0
16
0
Order By: Relevance
“…These findings led to the hypothesis of a tumour suppressive role for CAR in human cancers. In line with this hypothesis, reduced presence of CAR was found in advanced cancers in part associated with loss of tumour differentiation, increased infiltration, and a poor prognosis Sachs et al, 2002;Matsumoto et al, 2005;Korn et al, 2006;Buscarini et al, 2007;Okegawa et al, 2007). In gastric adenocarcinomas, an immunohistochemical analysis of cancer tissues from 30 patients and 11 non-cancerous controls showed reduced CAR staining intensities in gastric cancer (Heideman et al, 2001).…”
mentioning
confidence: 64%
“…These findings led to the hypothesis of a tumour suppressive role for CAR in human cancers. In line with this hypothesis, reduced presence of CAR was found in advanced cancers in part associated with loss of tumour differentiation, increased infiltration, and a poor prognosis Sachs et al, 2002;Matsumoto et al, 2005;Korn et al, 2006;Buscarini et al, 2007;Okegawa et al, 2007). In gastric adenocarcinomas, an immunohistochemical analysis of cancer tissues from 30 patients and 11 non-cancerous controls showed reduced CAR staining intensities in gastric cancer (Heideman et al, 2001).…”
mentioning
confidence: 64%
“…In several human carcinomas, particularly in more advanced stages, a reduced CAR presence was found, partially associated with loss of tumour differentiation, increased infiltration, and poor prognosis (Sachs et al, 2002;Matsumoto et al, 2005;Korn et al, 2006;Buscarini et al, 2007;Okegawa et al, 2007;Anders et al, 2009). On the basis of data from studies in cell lines, it has been speculated that loss of CAR promotes the proliferation, migration, and invasion of cancer cells (Okegawa et al, 2000(Okegawa et al, , 2001Runnebaum, 2003, 2004;Huang et al, 2005;Wang et al, 2005).…”
mentioning
confidence: 99%
“…To date, the role of CAR in breast cancer and the factors regulating CAR expression are poorly understood. Previous studies have shown that treatment of cancer cells with histone deacetylase inhibitors upregulates CAR expression (Kitazono et al 2001, Hemminki et al 2003, Pong et al 2003, Okegawa et al 2007. Other signals such as the MAPK pathway, the action of glucocorticoids, tumour necrosis factor a, and transforming growth factor-b also modulate CAR expression (Anders et al 2003, Bruning & Runnebaum 2003.…”
Section: Discussionmentioning
confidence: 99%